Preparation of Magnesium‐Seamed C‐Alkylpyrogallol[4]arene Nanocapsules with Varying Chain Lengths. Issue 35 (30th May 2017) - Zhang, Chen; Patil, Rahul S.; Li, Tao; Barnes, Charles L.; Teat, Simon J.; Atwood, Jerry L.
Abstract: Novel supramolecular nanocapsules based on metal‐directed assembly have captured tremendous interest due to their applications in fields such as catalysis, selective gas adsorption, and biomedicine. Functionalization of metal–organic nanocapsules (MONCs) by using organic ligands with different pendant groups affords more complexity to the structure and may lead to novel properties. In this work, we report the solvothermal synthesis of a group of magnesium‐based MONCs using C ‐alkylpyrogallol[4]arenes with varying alkyl chain lengths. The structures of these nanocapsules are characterized by single‐crystal X‐ray diffraction analysis. As expected, a progression in size of the nanocapsules is observed as the alkyl chain length increases. The effect of the chain length on the solubility of MONCs in water has been determined. This work shows the generality of the solvothermal approach for the synthesis of MONCs with different organic ligands and demonstrates that surface functionalization of MONCs may serve as an effective way to tailor their properties. The unique biocompatible nature and inherent large cavity of these magnesium‐based MONCs make these nanocapsules promising for potential applications in biomedicine. Abstract : Metal–organic nanocapsules : The solvothermal synthesis is presented of a class of magnesium‐seamed nanocapsules using C ‐alkylpyrogallol[4]arenes with varying alkyl chain lengths. As expected, a progression in size of nanocapsules across extended chains is observed. Lower water solubility of the nanocapsules is found as the tail length increases.